Development of a mobile camera application for long exposure photography - Lu, Yiting (Nanyang Technological University, 2024)
In this project, an Android mobile application capable of producing high-quality long exposure images has been developed. The development process involved utilizing the Java programming language within the Android Studio integrated development environment (IDE) and leveraging the Software Development Kit (SDK) for design purposes. Furthermore, the integration of OpenCV algorithms such as ORB (Oriented FAST and Rotated BRIEF) algorithm along with ECC (Enhanced Correlation Coefficient) algorithm was successfully implemented to perform tasks such as image stacking and alignment, streamlining the creation of a unified final image from multiple source images. Moreover, a server written in Go Lang is developed on Visual Studio Code IDE to serve as a link between the mobile camera application and the image post-processing algorithm in Python.